The Influence of Religiosity, Income And Consumption on Saving Behaviour: The Case of International Islamic University Malaysia (IIUM) - Naziruddin Abdullah; M. Shabri Abd.Majid (Jurnal Iqtisad, 2003)
Islam encourages its ummah to consume goods and services moderately, and prohibits them from wastage or extravagance. With these encouragements and prohibitions firmly embedded in the teachings of Islam, it is expected that the Muslims will save more out of their given income. Further, the limitation of consumption basket within the Islamic concept of permissibility (halal) and prohibition (haram), the potentiality of saving amongst the Muslims is obviously enhanced. This will in turn imply that a practising Muslim (i.e., the Muttaqin) who obeys all the shari’ah injunctions will tend to save more than the ignorant Muslims, cateris paribus. With this in mind, the paper attempts to measure the influence of religiosity, income and consumption on saving behaviour. To make the study materializes, the IIUM students, Malaysian and international, are taken as the case study. From the empirical results, it is found that the religiosity and other variables have a significant impact on the IIUM students’ saving behaviour. The inference of the finding is that such a relationship, for example, between religiosity and saving may exist if the study is extended to investigate the saving behaviour of Muslims with different credentials.Key words: Saving behaviour, Religiosity, Consumption and Income.